Respons Pemberian Pupuk Hayati dan NPK terhadap Pertumbuhan dan Produksi Tanaman Kedelai (Glucine max (L) Merrii): Response of Biological Fertilizers and NPK to the Growth and Production of Soybean (Glycine max (L) Merrii) (Jurnal Agroekoteknologi dan Agribisnis, 2023)
The aim of the study was to determine the effect of biological fertilizers and NPK on the growth and production of soybeans. As an alternative to reducing the use of chemical fertilizers. The design used was a Factorial Randomized Block Design, which consisted of two factors, namely the Biological Fertilizer (H) with a dose of 82 ml of solution / plot consisting of 4 levels, namely: H0 = (control) , H1 = 2 Weeks After Planting, H2 = 3 Weeks After Planting, H3 = 4 Weeks After Planting and NPK Fertilizer Factor (N) with 3 treatment levels, namely N1 = 30 grams/plot (50% of recommended dose), N2 = 45 grams/plot (75% of the recommended dose), N3 = 60 grams / plot (100% of the recommended dose). The parameters observed were plant height, number of pods planted, number of pods per plot, number of seeds planted, number of seeds per plot, and weight of 100 seeds. The results showed that the application of biofertilizers had a significant effect on pod weight per plant, but had no significant effect on plant height, pod weight per plot, seed weight per plant, seed weight per plot, and weight of 100 seeds. soya bean. The best application of biological fertilizers was obtained in the H2 treatment, namely the provision of biological fertilizers 2 weeks before planting and given again 2 weeks of biological fertilizers after planting. The application of NPK fertilizer did not significantly affect plant height, pod weight per plant, pod weight per plot, seed weight per plant, seed weight per plot, and weight of 100 seeds. The best application of NPK fertilizer was obtained at treatment N3 = 60 grams/plot (100% of the recommended dose).